Central Banking in the Light of Recent British and American Experience - Sayers, R. S. (Quarterly Journal of Economics, 1949)
I. Introduction, 198. — II. Central bank control during the inter-war period, 198 — III. More recent problems: control of long-term interest rates in Britain and the United States, 201. — IV. Selective credit policy as a supplement to low and stable interest rates, 206. — V. This policy not a complete break with the past, 209. — VI.